Pemanfaatan Software SLiMS (Senayan Library Management System) di UPT Perpustakaan Kopertis Wilayah X (Sumatera Barat, Riau, Jambi, dan Kepulauan Riau) - Rahmadhani, Dahlia; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The purpose of writing this article is to describe: (1) how the utilization of software SLiMS by librarians in UPT kopertis Library Region X; (2) how the workings of SLiMS in UPT Kopertis Library Region X; (3) what are the constraints of the use of SLiMS in UPT Kopertis Library Region X; (4) give the effort from the constraints of the use of the SLiMS in UPT Kopertis Library Region X. Data collected through direct observations, and conducting interviews with librarians UPT Kopertis Library Region X. Based on data analysis can be summed up as follows: (1) utilization of SLiMS in UPT Kopertis Library Region X includes search OPAC, circulation, bibliography, and membership management; (2) the workings of SLiMS in UPT Kopertis Library Region X IE is search through OPAC, circulation, membership management, classification and label printing of the book. Constraints of the use of the SLiMS are; (1) lack of librarians who have the ability to use software SLiMS; (2) lack of facilities or support tools for SLiMS as sensors, scanning, printing tools and tool card barcode printing; (3) the absence of generator sets to anticipate when the electricity is off. The efforts of the constraints is done in the use of SLiMS is;(1) provide specific training to librarians about the use of the software SLiMS properly; (2) completes the facilities and supporting tools needed by librarians in running SLiMS software; (3) the need for generator sets in anticipation of electricityÂ Keywords: Software SLiMS (Senayan Library Management System)